2003
DOI: 10.1637/0005-2086-47.s3.806
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Highly Pathogenic Avian Influenza in Australia in 1997 Caused by an H7N4 Virus

Abstract: In November of 1997 an outbreak of highly pathogenic avian influenza occurred near the town of Tamworth, in northern New South Wales, Australia. The viruses isolated from chickens on two commercial chicken farms were identified as H7N4 viruses, with hemagglutinin cleavage site amino acid sequences of RKRKRG and intravenous pathogenicity indices of 2.52 and 2.90, respectively. A virus with an identical nucleotide sequence, but with an intravenous pathogenicity index of 1.30, was also isolated from cloacal swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 3 publications
0
69
0
Order By: Relevance
“…Other species normally not associated with the maintenance of avian influenza viruses are also occasionally infected (Table 1) (Stallknecht and Shane 1988). This has also occurred during outbreaks of HPAI, for example, Starlings (Sturnus vulgaris) (Nestorowicz et al 1987), ratites (Selleck et al 2003) and flamingos, falcons and crows during the 2003-04 Asian epidemic.…”
Section: Occurrence Of Avian Influenza In Wild Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species normally not associated with the maintenance of avian influenza viruses are also occasionally infected (Table 1) (Stallknecht and Shane 1988). This has also occurred during outbreaks of HPAI, for example, Starlings (Sturnus vulgaris) (Nestorowicz et al 1987), ratites (Selleck et al 2003) and flamingos, falcons and crows during the 2003-04 Asian epidemic.…”
Section: Occurrence Of Avian Influenza In Wild Birdsmentioning
confidence: 99%
“…1986) and 1992 (Selleck et al . 1997) in Victoria, in 1994 in Queensland (Westbury 1998), and in 1997 in Tamworth, New South Wales (Selleck et al . 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, type H7 antibodies were not detected nor was the virus isolated (details including sample number are not shown) (Selleck et al 2003 (6) Cases in which the same type of virus was observed in wild birds prior to outbreaks of avian influenza involving domestic fowl Type H7N2 virus was isolated from 15 dead wild mallards in Israel in 1979 and, at the same time, outbreaks of the same type involving turkeys were observed in an adjacent area (Lipkind et al, 1979). In tests conducted in the U.S. in 1980-81, when mallards that had tested negative were put together with turkeys, virus (H4N8, H4N2, H5N2) was isolated from the mallards before or at the same time that avian influenza of the same type viruses was detected in the turkeys.…”
Section: Wild Bird Virus Tests Following Avian Influenza Infection Inmentioning
confidence: 99%
“…We hypothesise that it is during this period of increasing densities of serologically naïve birds that AIV prevalence increases dramatically within wild populations and provide the source of infection in domestic poultry flocks. Australia has experienced five outbreaks of HPAI in poultry since 1976 all of which were caused by H7 viruses (Selleck et al 2003;Hamilton et al 2009), for which the ancestral reservoir is hypothesised to reside within Australia (Bulach et al 2010). Following the introduction of LPAI viruses (H7 or H5) into poultry flocks via wild birds, conditions in poultry farms then provide ideal conditions for development of HPAI strains (Alexander 2007a).…”
Section: What Role Do Resident Birds Play In the Ecology And Epidemiomentioning
confidence: 99%
“…Following the introduction of LPAI viruses (H7 or H5) into poultry flocks via wild birds, conditions in poultry farms then provide ideal conditions for development of HPAI strains (Alexander 2007a). In at least two of the five outbreaks, direct contact with Australian wild waterfowl was implicated as the source of the outbreak (Selleck et al 2003;Hamilton et al 2009). Besides direct contact between waterfowl and poultry, intermediate avian hosts from a wide range of bird species that have high contact rates with both freshwater habitats and poultry may play a role in the transmission of these viruses between waterfowl and poultry Gronesova et al 2008;Peterson et al 2008;Hoye et al 2010b).…”
Section: What Role Do Resident Birds Play In the Ecology And Epidemiomentioning
confidence: 99%